Assessment of the knowledge of the subjects of the training process about psychological preparation in sports - Levina, I. L.; Artemiev, A. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the level of knowledge about the process and content of the psychological preparation of athletes among the subjects of the educational process, including athletes, coaches and parents of athletes.